Obesity : preventing and managing the global epidemic : report of a WHO consultation (WHO, 2000)
This report issues a call for urgent action to combat the growing epidemic of obesity, which now affects developing and industrialized countries alike. Adopting a public health approach, the report responds to both the enormity of health problems associated with obesity and the notorious difficulty of treating this complex, multifactorial disease. With these problems in mind, the report aims to help policy-makers introduce strategies for prevention and management that have the greatest chance of success. The importance of prevention as the most sensible strategy in developing countries, where obesity coexists with undernutrition, is repeatedly emphasized.Recommended lines of action, which reflect the consensus reached by 25 leading authorities, are based on a critical review of current scientific knowledge about the causes of obesity in both individuals and populations. While all causes are considered, major attention is given to behavioural and societal changes that have increased the energy density of diets, overwhelmed sophisticated regulatory systems that control appetite and maintain energy balance, and reduced physical activity. Specific topics discussed range from the importance of fat content in the food supply as a cause of population-wide obesity, through misconceptions about obesity held by both the medical profession and the public, to strategies for dealing with the alarming prevalence of obesity in children.The report has eleven chapters presented in five parts. Part one, which assesses the magnitude of the problem, explains the system for classifying overweight and obesity based on the body mass index, considers the importance of fat distribution, and provides an overview of trends in all regions of the world, concluding that obesity is increasing worldwide at an alarming rate. Chapters in part two evaluate the true costs of obesity in terms of physical and mental ill health, and the human and financial resources diverted to deal with these problems. Specific health consequences discussed include increased risk of cardiovascular disease, cancer, and other noncommunicable diseases, endocrine and metabolic disturbances, debilitating health problems, and psychological problems. The health benefits and risks of weight loss are also assessed.Part three draws on the latest research findings to consider specific factors involved in the development of overweight and obesity. Discussion centres on factors, such as high intakes of fat, that may disrupt normal physiological regulation of appetite and energy balance, and the role of dietary factors and levels of physical activity. In terms of opportunities for prevention, particular attention is given to the multitude of environmental and societal forces that adversely affect food intake and physical activity and may thus overwhelm the physiological regulatory systems that keep weight stable in the long term. The possible role of genetic and biological susceptibility is also briefly considered.Against this background, the fourth and most extensive part maps out strategies for prevention and management at both the population and individual levels. Separate chapters address the need to develop population-based strategies that tackle the environmental and societal factors implicated in the development of obesity, and compare the effectiveness of current options for managing overweight or obese individuals. Specific strategies discussed include dietary management, physical activity and exercise programmes, behaviour modification, drug treatment, and gastric surgery. While noting striking recent progress in the development of drug treatments, the report concludes that gastric surgery continues to show the best long-term success in treating the severely obese. The final part sets out key conclusions and recommendations for responding to the global obesity epidemic and identifies priority areas where more research is urgently needed.\"... the volume is clearly written, and carries a wealth of summary information that is likely to be invaluable for anyone interested in the public health aspects of obesity and fatness, be they students, practitioner or researcher.\" - Journal of Biosocial Science
WHO technical report series, ISSN 0512-3054 894
Keywords: výživová politika; vnitřní lékařství; obezita; National Health Programs; Cost of Illness; Obesity; nutriční terapie, dietoterapie a výživa; endokrinologie; Nutrition Policy; osobní újma zaviněná nemocí; programy národního zdraví; veřejné zdravotnictví